N- and P- type Doping in Al-rich AlGaN and AlN. (23rd July 2018) - Sarkar, Biplab; Washiyama, Shun; Breckenridge, M. Hayden; Klump, Andrew; Baker, Jonathon N.; Reddy, Pramod; Tweedie, James; Mita, Seiji; Kirste, Ronny; Irving, Doug L.; Collazo, Ramon; Sitar, Zlatko
Abstract : Attaining a high conductivity in both p-type and n-type Al-rich AlGaN epitaxial films is necessary for highly efficient deep-UV emitters. While reliable n-type conductivity has been demonstrated in Alx Ga1-x N up to x < 0.8, achieving a reasonable p-type conductivity is a challenge even in Ga-rich AlGaN films. As one increases the x in Alx Ga1-x N, several point defects and charge compensators appear in the epitaxial film. This report reviews recent observations on doping, conductivity, point defect control of Al-rich AlGaN films. Discussions on activation energy, state-of-the-art epitaxial material quality, contact formation and surface treatments are also presented.